Implementation of an HRIMS at the Personnel Board of Jefferson County, Alabama: A Case Study in Process Reengineering. - McCullough, Roger; Sims, Ronald R. (Public Personnel Management)
This paper presents a case study of how a human resource information management system (HRIMS) was implemented in a civil service agency. The paper first describes the five-phases of the business reengineering process used to implement the HRIMS. It concludes with lessons learned for implementing an HRIMS in public sector organizations.